A Comparison of Capillary and Venous Blood Haematocrits of Pregnant Women in Nigeria: The Impact on Diagnosis and Prevalence of Anaemia in Pregnancy. (28th January 2014) - Dim, Cyril Chukwudi; Ugwu, Emmanuel Onyebuchi; Anyaehie, Ugochukwu Bond; Obioha, Kingsley Chukwu
Abstract : Background . Volume of red cells in capillary blood varies from that of venous blood. The magnitude of this variation as well as its impact on the diagnosis of anaemia in pregnancy needs to be studied. This study demonstrates the disparity between capillary and venous PCV in pregnancy. Objectives . To determine whether capillary blood PCV (cPCV) differed from venous blood PCV (vPCV) of normal pregnant women in Enugu, Nigeria, and its effect on diagnosis and prevalence of anaemia. Methods . PCV was estimated using pairs of venous and capillary blood samples from 200 consecutive pregnant women at the Antenatal Clinic of University of Nigeria Teaching Hospital, Enugu, Nigeria. Results . Participants' cPCV ( m e d i a n = 34.0 %, I Q R = 31.0 – 35.8 ) was significantly lower than their vPCV ( m e d i a n = 34.0 %, I Q R = 32.0 – 37.0 ) (Z = - 6.85, P < 0.001 ). However, women's cPCV had strong positive correlation with their vPCV (r = 0.883, P < 0.001 ). The prevalence of anaemia among participants using capillary and venous blood was 33.5% (67/200) and 28.0% (56/200), respectively (O.R = 1.3 (CI 95%: 0.85, 1.98),   P = 0.233 ). Conclusions . Capillary blood PCV was lower than vPCV among pregnant women in Enugu, Nigeria. Nevertheless, the prevalence of anaemia derived from cPCV did not differ significantly from that of vPCV.